The Role of Customary Leaders on the Decision Making Process in the Ethics of Land Clearing and Harvesting Process in Rice Farmers in Puday Village, Wonggeduku Barat Sub-District, Konawe District - H. Helviani; H. Husnaeni (Universitas Sembilanbelas November Kolaka, 2018)
Customary leaders have dominant roles and influences, these facts are shown in the land clearing process (monahundau) and the harvesting process (meolu) of paddy rice crop. These processes begin with the opening ceremony or in the form of a small ritual carried out by customary leader numbering one person called Puusaraormandaranosara. The purpose of this study is to find out how the role of customary leaders in decision-making in the ethics of land clearing and harvesting processes in paddy rice farmers. Analysis of the data used in the form of qualitative descriptive analysis, where the data obtained is then described qualitatively using the Miles and Huberman model which consists of three stages, namely (1) Data Reduction, (2) Data Presentation, (3) Conclusion Drawing / Verification. The results of this study indicated that land clearing (monahundau) and the harvesting process (meolu) were influenced by hereditary customs in Puday Village, Wonggeduku Barat Sub-District, Konawe District. Monahundau is a land clearing process which is the first step to open a new planting season every year. Meoluis a harvesting process that is carried out in the same steps as the process of land clearing (observation, reciting intentions and praying silently for the best wishes desired in the harvesting process), and the final step is done by investigating at the rice fields who first turned yellow (ripe), then the rice fields that will be harvested first, the rice begins to be harvested when there is already a statement then the other farmers' land that has yellowed (ripe) may be harvested by themselves (meoludowo). Customary leaders are people chosen by the people of Puday village (puusaraormandaranosara) and have an influnce on decision making in the process of land clearing (monahundau) andharvesting (meolu)